Properties of gadolinium-doped PZT(Zr:Ti=52:48) - S. Boonyuen (2018)
PZT(Zr:Ti=52:48) ceramics can be modified by Gd3+, giving compositions Pb1-xGdx-(Zr0.52Ti0.48)1-x/4O3with x = 0.00, 0.01, 0.5, 1, 2, 6 and 10 mole percent. X-ray diffraction patterns show that all PGZT samples are of tetragonal structure and the highest doping should be no more than 2 mole percent Gd at which impurity unreacted oxides start to appear. ESR spectra of PGZT's indicate that Gd3+can enter both A and B sites of the perovskite structure instead of only A site as widely believed. As a result, the tetragonality (c/a ratio) first increases and reaches a maximum at x ≅ 0.8 mole percent and drops as Gd3+enters more A sites. The doping should, however be limited to one mole percent as overdoping proves detrimental to the dielectric and piezoelectric properties of PGZT. The dielectric constant (1 kHz) of the poled samples reaches a maximum value of 1150 at x = 0.02 while the largest d33value of 160 pC/N is achieved at only lightly doped 0.01 mole percent. Furthermore, the Gd doping has a drastic effect on Qmand the dissipation factor DF - the former drops sharply while the latter increases with x.